ANALISIS FAKTOR KEAMANAN PADA JEMBATAN KERETA API BH NOMOR 105 KM 49+093 ANTARA STASIUN LUBUKALUNG DAN STASIUN SICINCIN DI DIVRE 2 SUMATERA BARAT - Dicky Arisikam; Heru Kuswanto; Muhammad Arifudin; Alya Ramadianisa (Jurnal Ilmiah Teknologi Infomasi Terapan, 2023)
One of the structures on various railroads, of which is a bridge. On the railway bridge, there are calculated loads. The load is divided into three, namely the girder self-load, additional dead load, and live load. Locomotives and wain have different axle loads and axle distances, so there is a change in the forces acting on the rail structure. Currently, the planned train loading is based on the 1921 Load Plan (RM) scheme. On the bridge BH No. 105 which connects Lubukalung Station with Sicincin is passed by BB 303 locomotive and closed wain, loading analysis is carried out by making axle loads and axle distances on a span of 50 m. Then we can compare the calculation of the load with the RM 1921 and RM Sumbar scheme, it is necessary to check the capacity of the entire bridge structure against the applicable loading. Obtained the value of the calculation of the safety factor of the existing loading with the RM 1921 scheme for a maximum reaction is 2,353 and a maximum moment is 2,32. With the RM Sumbar scheme, a maximum reaction is 0.8365 and a maximum moment is 0.74125. This shows the achievement of a safety factor of more than 1.5 for the calculation of the safety factor of the existing loading with the RM 1921 scheme. While the maximum displacement safety factor value for the RM 1921 scheme is 0.005, West Sumatra RM 0.005, and the existing charge is 0.0667. Based on the calculation results, it is smaller than the maximum safety factor value that meets the requirements.